Anemia Disease Carrión - Hurtado, Alberto (1938)
Carrion's disease or Peruvian wart is being, some time ago, a fertile field of study for national and foreign researchers. Its restricted distribution; the controversial nature of some clinical and pathological stages; the heroic sacrifice of Daniel A. Carrión, young medical student who gave birth in an effort to elucidate problems of a fundamental nature; and severe anemia, unique in many of its characters, which develops in a significant number of cases, the researcher explain why interest in this process.